Being a researcher is not only a matter of publishing: learning to review scientific articles / No solo de publicar viven los investigadores: aprender a revisar artículos científicos. Issue 3 (3rd July 2017) - Castelló, Montserrat; Sala-Bubaré, Anna; Bautista, Alfredo
Abstract: This study, which is part of the call for junior reviewers from Infancia & Aprendizaje (I&A), aims to contribute to the scarce literature on peer review processes by developing and analysing a training proposal designed to help junior researchers begin to take part in the peer review process. Five junior reviewers participated in the study. Their reports were analysed and compared with those of 10 experts, their individual trajectories were described, and their evaluation of the training proposal was explored. Results showed some particularities in the junior reviewers' reports regarding their content and structure, such as the inconsistency between the decision taken and the type of comments. In addition, the junior reviewers' adoption of a personal opinion position was not observed in the expert reviewers. Their individual trajectories showed the relevance of the training proposal, both to increase knowledge about the genre and to revise the reports. This study has implications for scientific journals as well as for the training of junior researchers.